Relationship Between Authentic Leadership and Classroom Management in Public and Private Sector Universities (Journal of Education and Educational Development, 2020)
The study aims at to explore the authentic leadership attributes (ALA) and its impact on classroom management. The objectives of the study were to investigate ALA of leaders and measure relationship between ALA and classroom engagement at university level. The population of the study was 6975 leaders and teachers. The sample of the study was 967. The mixed method approach (convergent parallel design) was used to collect information from sample through modified form of Authentic Leadership Questionnaire (ALQ) developed by Walumbwa, Avolio, Gardener, Wernsing, & Peterson (2008) and in-depth interviews. Analysis was done with percentage, Mean, STD, independent sample t-test, one way ANOVA, Pearson’s rank correlation and thematic analysis. It was found that r value (.426) which was significant at .000 showed significant positive and average level correlations between ALA and classroom engagement at university level. Based on the results, it is recommended that it may be well to conduct research study on the authentic leadership at primary level, secondary level and college level both at private and public sectors as these areas are in great need of authentic leadership because these sectors suffered a lot due to unethical attitude of the leaders.